(untitled) (Global Journal of Medical Research, 2014)
Saffron is known as the majestic functional Natural Medicine, Saffron Extract is considered important for drug development, because they are reported to have Pharmacological activity in the Asia, Middle East especially China, Spain and India. For a long time Saffron has been used in traditional medicine for the relief of pain changing the mood and its use in cancer treatments, Saffron comes from the dried red stigmas of the Crocus sativus L. flower. Along with its use in cooking and in traditional medicine, it has numerous applications as an antitoxic, anti-oxidant, and anti-cancer agent, due to its secondary metabolites and their derivatives (safranal, crocins, crocetin, dymethylcrocetin). Data from this study will demonstrate that Crocus sativus extract (CSE) and its major constituents, crocin and crocetin significantly inhibited the growth of certain cancer cells while not effecting normal cells. Crocus sativus L. extract should be investigated further as a viable agent in the treatment of prostate, pancreatic or other types of cancer. This article presents comprehensive analysis information on botanical, chemical and Pharmacological aspect of Saffron.